Aplikasi Sistem Neuro-Fuzzy untuk Pengenalan Kata - TDS, Yohanes; , Thiang; Chandra, Suntono (Institute of Research and Community Outreach, 2002)
This paper describes implementation of neuro-fuzzy system, a hybrid system between neural network and fuzzy logic. In this research, neuro-fuzzy system is implemented for speech recognition. The words that would be recognized are